The Quranic Employment in the Poetry of Ahmad Matar - حافظ المنصوري (آداب الكوفة, 2012)
Since I looked at the complete collection of poetry by the contemporary Basri poet (Ahmed Matar), I was impressed with what this collection contains of pearls and treasures, and because of my great admiration for it, I wrote this phrase on its first page ((To Ahmed Matar, I found myself in you, and I was more impressed every time I came back Reading in it, and as a result, I had more than a modest tour with Ahmed Matar's poetry. This research topic (Quranic Employment in Ahmed Matar's Poetry)) was the outcome of this admiration. This subject and the poet's method in dealing with the Qur'anic text and his striking and ingenious style stopped me, which prompted me to study it, and the result of this research, which came in four topics.